2015
DOI: 10.1002/anie.201508461
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3: A Lewis Acid that Brings the Light to the Solid State

Abstract: The straightforward coordination of the Lewis acid B(C6F5)3 to classical, non-emitting aldehydes results in solid-state photoluminescence. Variation of the electronic properties of the carbonyl moieties lead to the modulation of the solid-state emission colors, covering the entire visible spectrum with quantum yields up to 0.64. Steady-state spectroscopy in combination with X-ray diffraction analysis and DFT calculations confirm that intermolecular interactions between the Lewis adducts are responsible for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…In this way, we demonstrated the ability to precisely control the excited‐state energy, by changing the strength or amount of the Lewis acid additive and by synthetically controlling the binding site of the chromophore. Around the same time, it was shown that coordination of B(C 6 F 5 ) 3 to non‐emissive aldehydes could engender intense color‐tunable luminescence, further highlighting the ability of Lewis acid‐base coordination chemistry to influence photophysical attributes …”
Section: Introductionmentioning
confidence: 88%
“…In this way, we demonstrated the ability to precisely control the excited‐state energy, by changing the strength or amount of the Lewis acid additive and by synthetically controlling the binding site of the chromophore. Around the same time, it was shown that coordination of B(C 6 F 5 ) 3 to non‐emissive aldehydes could engender intense color‐tunable luminescence, further highlighting the ability of Lewis acid‐base coordination chemistry to influence photophysical attributes …”
Section: Introductionmentioning
confidence: 88%
“…[8,9] The pyridyl nitrogen atom of PyBTM acts as as timulus-responsive site. [21][22][23] The coordination and dissociation of B(C 6 F 5 ) 3 to and from the nitrogen atom of PyBTM was expected to reversibly change the emission colour. [14,30] In this study,w eh ave tackled two challenges that had not previously been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The first concerns reversible control of the emission colouro ft he radical by usingB (C 6 F 5 ) 3 as an externalc hemical stimulus.B (C 6 F 5 ) 3 is aL ewis acid capable of reversibly binding aL ewis base, such as the lone pair of an itrogen atom, through the vacant 2p Z orbital [18][19][20] and has been used as an additive to modulate the optical properties of molecularm aterials. [21][22][23] The coordination and dissociation of B(C 6 F 5 ) 3 to and from the nitrogen atom of PyBTM was expected to reversibly change the emission colour. The second challenge is elucidating how the chemical modificationa ffectst he electronic structure (electron density distribution and energy levels of molecular orbitals)i nm odulating the properties of radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few successful demonstrations of solid-state emission induced by non-covalent interactions have been reported. These include a coordination bond between the p-orbital of borane compounds and the oxygen atom of aldehydes 18 , acid-base interactions 19 , isolation of uorescent dyes by ionic lattices 20 and an anion-π + interaction 21 . The introduction of electron-donating and electronwithdrawing groups to π-conjugated molecular systems with rotatable covalent bonds is a strategy for AIEE dye synthesis.…”
Section: Introductionmentioning
confidence: 99%